Use of Convalescent Plasma in Covi-19 Patients: Narrative Review: Convalescent Plasma - Aguilar, Rene (Journal of Medical Biomedical and Applied Sciences, 2021)
Abstract Convalescent plasma therapy has given good results with the patients under study, they have been able to support the symptomatic patient and quite encouraging results are obtained in their recovery. Articles from the last 9 months were reviewed in Google Scholar, PubMed and Scopus and those were selected that will help to understand its application and confirm that it is an alternative and complementary treatment to patients with Covid-19. It was found that there is abundant experimental and clinical literature on the use of convalescent plasma in different symptomatic stages of Covid-19, which merits testing with the established protocol the effect of its use in critical symptomatic patients who need the use of it, the value of antibodies IgG obtained from recovered patients can be helpful in aliquoting it, defining the minimum volume of placement to optimize it and exposing only what is necessary to the patient infected by infectious reactions that he may acquire in the future as a non-autologous product. Keywords: Aliquot, Integrative Medicine, Total IgG Levels, Plasmapheresis, Symptomatic.